Dental Therapists' Role in the Provision of Aesthetic Dentistry in Dental Practice. Issue 2 (June 2023) - Baker, Linzy; Valadas Marques, Arabella; Blum, Igor R.
Dental therapists have a vital role to play in the provision of dentistry in the UK. This article examines the role of dental therapists in carrying out aesthetic dentistry in the UK dental practice setting. Patient access through collaborative working, especially through a shared care model, referral, and direct access will be discussed. In addition, two clinical cases are presented to demonstrate the provision of aesthetic anterior dental restorations by dental therapists.